مولانا اصغر علی ربانی کی آسان تفسیر القرآن کے منہج و اسلوب کا تجزیاتی مطالعہ : An Analytical Study of the Format and Style of Maulana Asghar Ali Rabbani’s Simple Tafsir of the Qur’an - Hafiz Muhammad Akbar Ali; Dr Hafiz M. Mudassar Shafique; Hafiza Attiqa Shehzadi (Al Manhal Research Journal, 2025)
Moulana Asghar Ali Rabbani is an authentic and religious scholar.He completed his education at Dar-ul-aloom, Qasim ul- aloom in Multan Continuing his teaching process, he come to Dar-ul-aloom Karachi and served Islam till the last breath. Along with teaching, he also did some written work. He wrote books on Hadith, Tafseer and fiqa. He narrated all problems of tafseer in an easy way. The method/style of tafseer is easy and simple. First of all, the topic of Ayat, then word to word translation. The explanation of difficult words are described in simple and easy words in the tafseer. Grammer are described in simple way. He has also used either Tafaseer and Hadith Books. In this Tafseer, Difficult words are described and explained grammatical. The religious services of Moulana Asghar Ali Rabbani are worth-praising. He has written many books. But the books Asaan Tafseer ul- Quran and Jamai- Termizi-w-Al mazahib Hanfi got much frame. Other scholars have also commented on these books. His other books are also worth-praising. His style is easy to comprehend. He has narrated first of all, Topic of Ayat, word to word and Translation, Introduction of Surah, and summary it help from basic and secondary bibliography is taken in tafseer.